ANALISIS DILALAH LAFDZIYAH PADA ASMA’UL HUSNA DALAM SURAH AL-HASYR SERTA IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB - Muhamad Satrio; Fachrul Ghazi; Ahmad Basyori; Riski Gunawan (STKIP Subang, 2025)
This study is motivated by the limited number of linguistic studies examining Asmaul Husna in the Qur’an using a dalālah lafdziyah approach and by the underutilization of such studies in Arabic language learning. This research aims to analyze the meanings of Asmaul Husna in Surah Al-Hasyr from morphological and semantic perspectives and to explain their relevance to Arabic language instruction. The study employs a qualitative approach using a library research method. The primary data source is the Qur’an, specifically Surah Al-Hasyr, while secondary data are obtained from classical tafsir works, Arabic linguistics books, and relevant scholarly articles. Data were collected through documentation techniques and analyzed using descriptive-analytical methods with a thematic approach. The findings reveal that the Asmaul Husna in Surah Al-Hasyr contain both explicit and implicit meanings that are closely interconnected. Therefore, their meanings cannot be understood solely based on lexical definitions but must be interpreted within the context of the verses and the overall structure of the surah. This study concludes that dalālah lafdziyah analysis of Asmaul Husna has strong potential as a contextual resource for Arabic language learning, particularly in enriching vocabulary, enhancing semantic understanding, and fostering students’ spiritual values.